Sociodemographic, Epidemiological, and Clinical Risk Factors for Childhood Pulmonary Tuberculosis in Severely Malnourished Children Presenting With Pneumonia - Mohammod Jobayer Chisti MBBS, MMed, PhD; Tahmeed Ahmed MBBS, PhD; Abu S. M. S. B. Shahid MBBS; K. M. Shahunja MBBS; Pradip Kumar Bardhan MBBS, MD; Abu Syeed Golam Faruque MBBS, MPH; Sumon Kumar Das MBBS; Mohammed Abdus Salam MBBS (SAGE Publishing, 2015)
We aimed to evaluate sociodemographic, epidemiological, and clinical risk factors for pulmonary tuberculosis (PTB) in children presenting with severe acute malnutrition (SAM) and pneumonia. Children aged 0 to 59 months with SAM and radiologic pneumonia from April 2011 to July 2012 were studied in Bangladesh. Children with confirmed PTB (by culture and/or X-pert MTB/RIF) (cases = 27) and without PTB (controls = 81; randomly selected from 378 children) were compared. The cases more often had the history of contact with active PTB patient ( P < .01) and exposure to cigarette smoke ( P = .04) compared with the controls. In logistic regression analysis, after adjusting for potential confounders, the cases were independently associated with working mother ( P = .05) and positive tuberculin skin test (TST; P = .02). Thus, pneumonia in SAM children is a common presentation of PTB and further highlights the importance of the use of simple TST and/or history of contact with active TB patients in diagnosing PTB in such children, especially in resource-limited settings.